Communication Ethics in Social Spaces in QS Ṭāhā [20]:44: A Review through Toshihiko Izutsu’s Semantic Approach - Ilzam Hubby Dzikrillah Alfani; Jimmy Malintang; Axesa Haraja Saputra (Al-Qudwah: Jurnal Studi Al-Qur'an dan Hadis, 2026)
This study seeks to analyse the concept of qaulan layyina in Qur’an Surah Ṭāhā [20]:44 through the application of Toshihiko Izutsu’s semantic approach, with the aim of elucidating the construction of communication ethics within the Qur’anic framework. The significance of this research lies in addressing the growing prevalence of aggressive communication in social and digital contexts, which necessitates an ethical foundation for communication that is pertinent to contemporary life. While previous scholarship has predominantly examined qaulan layyina from normative and textual perspectives, few studies have employed Izutsu’s semantic analysis to explore this verse in relation to the Qur’anic worldview of communication. Utilising a qualitative methodology grounded in library research, this study analyses the basic, relational, synchronic-diachronic, and semantic field meanings of the term qaulan layyina. The findings indicate that qaulan layyina denotes not only ‘gentle speech’ at a lexical level but also functions as a central concept within the Qur’anic communication system, linking communicative actions, methods of message delivery, and the objective of the listener’s moral transformation. This concept is associated with related  terms such as qaulan ḥasanan, qaulan ma‘rūfan, qaulan karīman, and qaulan sadīdan, collectively constituting a system of communication ethics that emphasises gentleness, truthfulness, respect, and persuasion in contemporary social interactions. These results suggest that qaulan layyina may serve as a normative foundation for da‘wah practices, education, digital media, and the cultivation of courteous, persuasive, and constructive social relations. This study contributes to the enrichment of semantic tafsīr scholarship and offers a Qur’anic communication model of relevance to modern society.